Resonant near‐surface inertial oscillations in the northeastern Gulf of Mexico. Issue 4 (1st April 2016) - Gough, Matt K.; Reniers, A. J. H. M.; MacMahan, Jamie H.; Howden, Stephan D.
Abstract: The inertial frequency is nearly diurnal at 30°N latitude which transects the northeastern Gulf of Mexico (NeGoM). At this latitude, near‐surface inertial oscillations can amplify due to resonance with diurnal wind forcing. Diurnal oscillations have also been attributed to diurnal tidal forcing in this region. Because tidal forcing, wind forcing, and inertial oscillations are nearly diurnal, a unique series of comparative analyses are required to determine their relative influence on surface circulation. By comparing surface currents obtained by HF radar to predictions of the inertial response to wind forcing and barotropic tidal currents, it is found that diurnal oscillations in the NeGoM were predominantly due to wind‐forced inertial oscillations in June 2010. The analyses provide a unique spatiotemporal perspective of inertial oscillations in the NeGoM where there is evidence of propagation, frequency and phase shifts, and amplitude variability. Because inertial oscillations mix the ocean differently than the tides, these results provide insight into how inertial oscillations potentially mixed oil from the Deepwater Horizon spill in June 2010. Near‐diurnal oscillations during the winter were found to be predominantly due to tidal forcing when wind‐driven inertial oscillations were diminished due to a presumably deeper mixed layer. Key Points: Diurnal oscillations in the N.E. Gulf of Mexico are attributed to wind‐forced inertial motions The inertial motions exhibit evidence of propagation, enhancement related to flow, and phase shifts Variability of the inertial oscillations provides insight into how they mix the N.E. Gulf of Mexico